2002
DOI: 10.1007/s00167-002-0295-x
|View full text |Cite
|
Sign up to set email alerts
|

Pull-out and shear failure strengths of arthroscopic meniscal repair systems

Abstract: Meniscal repair is common and recommended in young patients. Suture techniques and fixation devices were developed for stronger, more facile repairs. Three devices (T-Fix, Meniscal Staple, Meniscus Arrow) were biomechanically compared to horizontal PDS suture. Peripheral tears were created in porcine menisci and repaired using the manufacturer's technique. An Instron was used to distract the menisci at 50 mm/min in axial-pullout and longitudinal shear loads. Load to failure curves and peak failure loads were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 24 publications
1
42
1
1
Order By: Relevance
“…5,9,17,35,78,80,81 Vertical sutures are superior to both horizontal sutures and meniscus arrows in mean load-to-failure values. 4,16,52,78 The superior strength of vertical sutures is hypothesized to be due to the perpendicular orientation to the circumferential collagen bundles of the meniscus.…”
Section: Operative Techniquesmentioning
confidence: 97%
“…5,9,17,35,78,80,81 Vertical sutures are superior to both horizontal sutures and meniscus arrows in mean load-to-failure values. 4,16,52,78 The superior strength of vertical sutures is hypothesized to be due to the perpendicular orientation to the circumferential collagen bundles of the meniscus.…”
Section: Operative Techniquesmentioning
confidence: 97%
“…[10] Zantop et al examined the difference between horizontal and vertical suture patterns by applying a cyclic load in shear. They found that horizontal suture had less elongation between cycles and higher load to failure than vertical sutures, but did not examine any of the all-inside devices.…”
Section: Discussionmentioning
confidence: 99%
“…This testing setup was modified from that previously described. [10] A pre-load of 2 N was applied and load-to-failure testing was performed at a constant displacement rate of 12.5 mm/sec. This displacement rate was consistent with previous studies that evaluated the ultimate pullout strength of sutures and suture anchors and is reflective of a rapid loading force.…”
Section: Biomechanical Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we standardised the meniscal areas to be tested (333.7±56.0 mm 2 ). After the application of Histoacryl to the 25 mm of the tear site, the remaining meniscal horns were excised in order to maintain this standardisation and to ensure that the repair device, not the meniscal tissue, provided the fixation's stability [13].…”
Section: Methodsmentioning
confidence: 99%